Al-doped ZnO ceramic sputtering targets based on nanocrystalline powders produced by emulsion detonation synthesis – deposition and application as a transparent conductive oxide material - Neves, Nuno Miguel Pinto (2015)
Transparent conducting oxides (TCOs) have been largely used in the optoelectronic industry due to their singular combination of low electrical resistivity and high optical transmittance. They are usually deposited by magnetron sputtering systems being applied in several devices, specifically thin film solar cells (TFSCs). Sputtering targets are crucial components of the sputtering process, with many of the sputtered films properties dependent on the targets characteristics. The present thesis focuses on the development of high quality conductive Al-doped ZnO (AZO) ceramic sputtering targets based on nanostructured powders produced by emulsion detonation synthesis method (EDSM), and their application as a TCO. In this sense, the influence of several processing parameters was investigated from the targets raw-materials synthesis to the application of sputtered films in optoelectronic devices. The optimized manufactured AZO targets present a final density above 99 % with controlled grain size, an homogeneous microstructure with a well dispersed ZnAl2O4 spinel phase, and electrical resistivities of ~4 × 10-4 Ωcm independently on the Al-doping level among 0.5 and 2.0 wt. % Al2O3. Sintering conditions proved to have a great influence on the properties of the targets and their performance as a sputtering target. It was demonstrated that both deposition process and final properties of the films are related with the targets characteristics, which in turn depends on the initial powder properties. In parallel, the influence of several deposition parameters in the film´s properties sputtered from these targets was investigated. The sputtered AZO TCOs showed electrical properties at room temperature that are superior to simple oxides and comparable to a reference TCO – indium tin oxide (ITO), namely low electrical resistivity of 5.45 × 10-4 Ωcm, high carrier mobility (29.4 cm2V-1s-1), and high charge carrier concentration (3.97 × 1020 cm-3), and also average transmittance in the visible region > 80 %. These superior properties allowed their successful application in different optoelectronic devices.